OP55 How Many Coronary Heart Disease Deaths in Poland in 2020 might be Prevented by Further Reductions in Population Risk Factor Levels?. (10th September 2013) - Bandosz, P; Guzman-Castillo, M; Capewell, S; Zdrojewski, T; Critchley, J; Rutkowski, M; O'Flaherty, M
Abstract : Background: Poland has experienced one of the most dramatic declines in coronary heart disease (CHD) mortality rates in recent decades. This decline reflects the use of evidence based treatments and, crucially, population wide changes in diet. Our aim is to explore the potential for further gains in Poland by achieving population wide reductions in smoking, dietary salt and saturated fat intake and physical inactivity levels. Methods: A validated and updated policy model was used to forecast potential decreases in CHD deaths by 2020 as consequence of lifestyle and dietary changes in the population. Data from the most recent Polish risk factor survey was used for the baseline estimates (2011). We modelled two different policy scenarios regarding possible future changes in risk factors: A) conservative scenario: reduction of smoking prevalence and physically inactivity rates by 5% between 2011 and 2020, and reduction of dietary consumption of energy from saturated fats by 1% and of salt by 10%. B) ideal scenario: reduction of smoking and physically inactivity prevalence by 15%, and dietary reduction of energy from saturated fats by 3% and of salt by 30%. We also conducted extensive sensitivity analysis using different counterfactual scenarios of future mortality trends. Results: Baseline scenarios: by assuming continuing declines in mortality and no future improvements in risk factors the predicted number of CHD deaths in 2020 would be approximately 13, 600 (95% CI 9838, 18184) while if mortality rates remain stable, the predicted number of deaths would approximate 22, 200 (7792, 26688). Conservative scenario. Assuming continuing declines in mortality, small changes in risk factors could result in approximately 1500 (688, 2490) fewer deaths. This corresponds to an 11% mortality reduction. Under the ideal scenario, our model predicted some 4, 600 (2048, 8701) fewer deaths (a 34% mortality reduction). Reduction in smoking prevalence by 5% (conservative scenario) or 15% (ideal scenario) could result in mortality reductions of 4.5% and 13.8% respectively. Decreases in salt intake by 10% or 30% might reduce CHD deaths by 3.0% and 8.6% respectively. Replacing 1% or 3% of dietary saturated fats by poly-unsaturates could reduce CHD deaths by 2.6% or 7.7%. Lowering the prevalence of physically inactive people by 5-15% could decrease CHD deaths by 1.2-3.7%. Conclusion: Small and eminently feasible population reductions in lifestyle related risk factors could substantially decrease future number of CHD deaths in Poland, thus consolidating the earlier gains.